Site selectivity and reversibility in the reactions of titanium hydrazides with Si-H, Si-X, C-X and H+ reagents: Ti=N(α) 1,2-silane addition, Nβ alkylation, Nα protonation and σ-bond metathesis. - Tiong, P; Nova, A; Schwarz, A; Selby, J; Clot, E; Mountford, P (2012)
We report a combined experimental and computational comparative study of the reactions of the homologous titanium dialkyl- and diphenylhydrazido and imido compounds Cp*Ti{MeC(N(i)Pr)(2)}(NNR(2)) (R = Me (1) or Ph (2)) and Cp*Ti{MeC(N(i)Pr)(2)}(NTol) (3) with silanes, halosilanes, alkyl halides and [Et(3)NH][BPh(4)]. Compound 1 underwent reversible Si-H 1,2-addition to Ti=N(α) with RSiH(3) (experimental ΔH ca. -17 kcal mol(-1)), and irreversible addition with PhSiH(2)X (X = Cl, Br). DFT found that the reaction products and certain intermediates were stabilised by β-NMe(2) coordination to titanium. The Ti-D bond in Cp*Ti{MeC(N(i)Pr)(2)}(D){N(NMe(2))SiD(2)Ph} underwent σ-bond metathesis with BuSiH(3) and H(2). Compound 1 reacted with RR'SiCl(2) at N(α) to transfer both Cl atoms to Ti; 2 underwent a similar reaction. Compound 3 did not react with RSiH(3) or alkyl halides but formed unstable Ti=N(α) 1,2-addition or N(α) protonation products with PhSiH(2)X or [Et(3)NH][BPh(4)]. Compound 1 underwent exclusive alkylation at N(β) with RCH(2)X (R = H, Me or Ph; X = Br or I) whereas protonation using [Et(3)NH][BPh(4)] occurred at N(α). DFT studies found that in all cases electrophile addition to N(α) (with or without NMe(2) chelation) was thermodynamically favoured compared to addition to N(β).